The GH/IGF-I Axis and Cognitive Changes across a 4-Year Period in Healthy Adults - Deijen, Jan Berend (International Scholarly Research Network, 2011)
After the age of 40, the amount of growth hormone in humans decreases. The reduced activity of the GH-IGF axis may play a role in age-related cognitive impairments. In the present study, mood and cognition of 30 healthy subjects (7 males, 23 females, aged 41–76 yr, mean age 60.9 ± 9.0) were examined twice. At baseline, we determined fasting blood levels of GH and IGF-I. Mood and cognitive status were assessed at baseline and after, on the average, 3 years and 9 months of followup. Working memory performance decreased over the years in the low IGF-group (P = .007), but not the high IGF-I group. Higher levels of GH were related with a better working memory at the second test (r = 0.42, P = .01) while higher levels of IGF-I tended to be related with a better working memory (r = 0.3, P = .06). The results suggest that higher serum levels of GH and IGF-I preserve the quality of working memory functions over the years.